A Novel Superabsorbent Polymer from Crosslinked Carboxymethyl Tragacanth Gum with Glutaraldehyde: Synthesis, Characterization, and Swelling Properties. (20th November 2021) - Bachra, Yahya; Grouli, Ayoub; Damiri, Fouad; Talbi, Mohammed; Berrada, Mohammed
Abstract : Nowadays, current global environmental problems include measures to eliminate or reduce the negative impact of chemicals from petroleum sources and, therefore, the use of materials from natural resources is increasingly recommended. In this context, natural-based superabsorbent polymers derived from polypeptides and polysaccharides have undergone chemical and biochemical modifications to improve their ability to absorb and retain large amounts of liquids. In the present paper, a new process has been used to overcome the side effects of radical polymerization in the manufacture of conventional polyacrylate superabsorbents (SAPs). Tragacanth gum (TG) was selected to prepare a new superabsorbent material (CMTG-GA) based on carboxymethyl tragacanth (CMTG) crosslinked with glutaraldehyde (GA). The characterization of the polymer was carried out by FTIR, TGA, XRD, and SEM. The effect of the amount of crosslinking agent and the pH on the water absorption capacity was also examined. Subsequently, swelling studies were performed using free swelling capacity (FSC) and centrifuge retention capacity (CRC) techniques in distilled water, tap water, and saline solution. The results showed that the CRC of the new material is not less than 42.1 g/g, which was observed for a ratio of 20% by weight of GA to CMTG. Likewise, the maximum absorption results were 43.9 and 32.14 g/g, respectively, for FSC and CRC at pH 8.0. In addition, a comparison of the swelling capacities of the synthesized product with a commercial SAP extracted from a baby diaper, well known in the Moroccan market, showed that the performances were very similar.